Feeding behavior and aggression in wild Siberut macaques (Macaca siberu) living under low predation risk. Issue 7 (2nd March 2015) - Richter, Christin; Gras, Pierre; Hodges, Keith; Ostner, Julia; Schülke, Oliver
<x xml:space="preserve">Abstract</x> Investigating which factors influence feeding competition is crucial for our understanding of the diversity of social relationships. Socio‐ecological models differ in their predictions whether predation risk directly influences feeding competition and which factors exactly predict contest competition. We investigated feeding competition in Siberut macaques (Macaca siberu), a species endemic to Siberut Island (West Sumatra, Indonesia). Siberut macaques experience low predation risk, as major predators (felids, raptors) are absent. They are therefore appropriate subjects to test the prediction that low predation risk reduces feeding competition. To estimate contest potential, we quantified size, spatial distribution and density of food plants, and the availability of alternative resources. We recorded behavior in food patches using a modified focal tree method. Food patches, sorted by decreasing average feeding group size, included large trees (40% of focal plant observations), lianas/strangler (16%), medium trees (9%), small (palm) trees (20%), and rattan (15%). Most food patches were clumped but occurred at low densities relative to the area of average group spread. Thus, availability of alternative food patches was low. Although food patch characteristics indicate high contest potential, the observed aggression rate (0.13 bouts between adults/h) was low relative to other primates. Average feeding group size was small relative to total group size, and feeding group size matched crown volume. Perceived predation risk was low, based on spatial and feeding behavior of juveniles. Together, these results suggest that predation risk may influence feeding competition. Social and temporal factors (patch feeding time), but not ecological factors (fruit abundance in patch and forest, alternative resources) predicted aggression frequency in food patches. Overall, comparative data are still relatively scarce, and researchers should collect more data on group spread, sub‐grouping, perceived predation risk, and aggression in food patches before we can draw final conclusions about the role of predation risk for feeding competition. Am. J. Primatol. 77:741–752, 2015. © 2015 Wiley Periodicals, Inc.